Ontogenetic variation in head morphology and diet in two snakes (Viperidae) from northeastern Argentina - Lopez, Maria Soledad (2013)
Snakes are highly diverse in head morphology and in the types of prey they eat. Species of the Viperidae family have a high degree of morphological specialization; however, some species specialize in feeding on a single or a few prey species whereas closely related organisms take a diverse array of prey taxa. We compared head morphology and diet throughout ontogeny in two species of the family Viperidae. Rhinocerophis alternatus (Yarará grande) had a highly specialized diet, feeding exclusively on mammals throughout its life. Bothropoides diporus (Yarará chica) fed on small prey such as amphibians and reptiles and on large prey such as mammals. Mature specimens differed significantly in snout–vent length (SVL) between species whereas juvenile specimens did not. A statistical comparison of head morphology showed differences between species in both juvenile and mature specimens. Linear regression analysis showed that head variability throughout ontogeny was greater in R. alternatus than in B. diporus. There were significant positive correlations between total length of prey in relation to SVL, head length, and head width of predator and they were higher in R. alternatus than in B. diporus. Our findings suggest ontogenetic morphological variation between R. alternatus and B. diporus and that this variation could be related to interspecific differences in eating habits. Therefore, our results agree with the hypotheses postulating that differences in morphology and diet between species could be influenced by genetic and phylogenetic constraints. However, further studies comparing sympatric species or species with their ancestors in terms of morphology and diet are necessary to confirm these results.